Comparative strategic management: An emergent field in international management - Luo, Yadong; Sun, J.; Wang, S. (2011)
In this article we present an important yet understudied field in international management-comparative strategic management across nations. Although the strategic management discipline traditionally uses the firm as a unit of analysis, and indeed firms within the same nation or industry are often heterogeneous, as argued by the resource-based view, we observe something more. We note a sustained and systematic pattern of strategic management issues at the national-level. We explicate that a unique bundle of national-level institutional, competitive and socio-cultural conditions function together with a repertoire of distinctive capabilities or weaknesses for most firms, incubating certain national-level patterns of corporate-, business-, and international-level strategies adopted by most firms within the nation. To further illustrate we use BRIC countries (Brazil, Russia, India and China) to showcase why and how we advance the study of comparative strategic management (CSM). In our quest to guide future research on CSM, we present a rudimentary yet overarching framework of comparative environments, comparative capabilities, and comparative strategies among firms operating in BRIC countries.